Some determinants of employee productivity / Nazihah Nasir - Nasir, Nazihah (2015)
The productivity of office worker is very important in organization since it can increase the level of productivity every day. The study was conducted at Universiti Teknologi MARA Perlis. The main purpose of this study is to examine the relationship of office productivity components which are comfort, office layout, interaction and distraction with productivity of office worker. The sample size of this research is 132 of office worker in Universiti Teknologi MARA. The researcher has been used Statistical Package Social Science (SPSS) version 20.0 to analyze the data and find the result by using the frequent distribution, reliability of measurement, Pearson correlation and as well multiple regression analysis. The finding of the study indicates that comfort and interaction are the most significant factors that will influence the productivity of office worker. Therefore, some of recommendation has been given for future improvement.